Axial D3-trishomocubane Derivatives with Potential: Dreams or Reality? - I. Sharapa, Dmitry; A. Levandovskiy, Igor; E. Shubina, Tatyana (Current Organic Chemistry, 2012)
The D3-trishomocubane is a unique high symmetrical chiral stabilomeric compound. Its derivatives have great potential to be used as scaffolds for drugs, in structure-oriented design, asymmetric catalysis, light-driven systems and much more. Axial substitution is the most useful method for this purpose but the least studied. This paper critically analyzes various synthetic strategies aiming at introducing substituents into C2/C9 positions of D3-trishomocubane. Herein we cover formation of trishomocubane skeleton and rearrangement of Cs-trishomocubanes. Based on a comprehensive retrosynthetic analysis a general synthetic scheme is proposed.
Keywords: quinones